2020
DOI: 10.1080/07391102.2020.1841680
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided identification of potential SARS CoV-2 main protease inhibitors from diterpenoids and biflavonoids of Torreya nucifera leaves

Abstract: SARS CoV-2 is the causative agent of the pandemic disease COVID-19. There is an urgent need for effective drugs or vaccines which can effectively combat this outbreak. The main protease (Mpro), a key component for the SARS CoV-2 replication, is considered to be one of the important drug targets for developing anti-COVID-19 drugs. This SARS CoV-2 Mpro/cysteine protease has high sequence similarity with the same protease from SARS CoV-1. Previously, it has been shown experimentally that eight diterpenoids and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 86 publications
2
21
0
Order By: Relevance
“…Rameshkumar et al (2021) reported that amentoflavone exhibited a binding affinity with a score of −8.1 kcal/mol against main protease. Consistently, additional work done on biflavonoids of Torreya nucifera leaves showed that amentoflavone had −9.2 kcal/mol binding affinity (Ghosh et al, 2020) .…”
Section: Main Protease (Mpro As a Targetmentioning
confidence: 54%
“…Rameshkumar et al (2021) reported that amentoflavone exhibited a binding affinity with a score of −8.1 kcal/mol against main protease. Consistently, additional work done on biflavonoids of Torreya nucifera leaves showed that amentoflavone had −9.2 kcal/mol binding affinity (Ghosh et al, 2020) .…”
Section: Main Protease (Mpro As a Targetmentioning
confidence: 54%
“…[ 5 ] On the other side, repurposing of various classes of natural products in several herbs for S-CoV-2 M pro inhibitor also showed promising results. These repurposings were mainly conducted through in silico approaches such as terpenoids from Cacospongia mycofijiensis ,[ 6 ] diterpenoids and bioflavonoids from Torreya nucifera ,[ 7 ] glycosylated flavonoids from various herbs, and saponins and tannins from various herbs. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no other MD simulations of paritaprevir–RBD and amentoflavone–RBD complexes. But, there are many stable MD simulations of the amentoflavone complex with the main protease (Ghosh et al, 2020 ; Lokhande et al, 2020 ; Mishra et al, 2020 ; Patil et al, 2021 ; Saravanan et al, 2020 ; Swargiary et al, 2020 ). For paritaprevir and simeprevir, stable MD simulations with the main protease and the uridylate-specific endoribonuclease (NSP15) have been obtained (Alamri et al, 2020 ; Khan, Jha, Amera, et al, 2020 ; Khan, Jha, Singh, et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, amentoflavone is an effective inhibitor (IC 50 ¼ 8.3 mM) of the SARS-CoV main protease (Ryu et al, 2010). In the recent in silico studies (Ghosh et al, 2020;Lokhande et al, 2020;Mishra et al, 2020;Patil et al, 2021;Peterson, 2020;Puttaswamy et al, 2020;Saravanan et al, 2020;Swargiary et al, 2020), amentoflavone has been reported to bind tightly to the main protease of SARS-CoV-2. There are also three docking studies targeting spike glycoprotein of SARS-CoV-2, in which amentoflavone was found among the hit compounds with the binding energies: À7.6 kcal/mol (Wei et al, 2020), À8.7 kcal/mol (Puttaswamy et al, 2020), and À10.2 kcal/mol (Rameshkumar et al, 2021).…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation